2002
DOI: 10.1046/j.1365-2516.2002.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

The natural history and antiviral treatment of hepatitis C in haemophilia

Abstract: People with haemophilia who received non-virucidally treated large-pool clotting factor before 1986 were infected with hepatitis C virus (HCV), previously referred to as non-A, non-B hepatitis. Approximately one-tenth of patients have been shown to clear infection naturally and shown persistently negative HCV PCR. Patients have been infected with genotypes 1, 2 and 3 reflecting the plasma donors in Northern Europe and the United States. Several studies have shown that HCV mono-infection has a very slow progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 32 publications
5
38
0
Order By: Relevance
“…This infection with HCV in the present subjects is thought to have occurred before 1989, as observed by Taki et al [27]. Therefore, the recent increase in the number of deaths from hepatic disease may be a natural consequence of infection with HCV [28]. Although the emerging risk of mortality from liver disease and liver cancer had already been observed among hemophiliacs with or without HIV-1 in the United Kingdom just before 1997 [29], it became evident after 1997 in Japan.…”
Section: Discussionsupporting
confidence: 56%
“…This infection with HCV in the present subjects is thought to have occurred before 1989, as observed by Taki et al [27]. Therefore, the recent increase in the number of deaths from hepatic disease may be a natural consequence of infection with HCV [28]. Although the emerging risk of mortality from liver disease and liver cancer had already been observed among hemophiliacs with or without HIV-1 in the United Kingdom just before 1997 [29], it became evident after 1997 in Japan.…”
Section: Discussionsupporting
confidence: 56%
“…Several studies have suggested that the course of hepatitis C infection is accelerated and that the disease may produce more severe hepatic damage in HIVcoinfected patients (10,30,196,204,254,319,324,(337)(338)(339)(340). These studies also demonstrate that patients infected with both viruses generally have higher circulating HCV viral burdens than do patients who are not HIV infected.…”
Section: Natural Historymentioning
confidence: 83%
“…Heat-inactivated factor concentrates were not available until November 1985. Virtually, all hemophiliacs who received clotting factor concentrates prior to implementation of viral inactivation techniques became infected with hepatitis C virus at the time of the first infusion (Morfini et al, 1994;Lee C et al, 2002;Ragni et al, 2010). Prevalence rates of HCV infection up to 100% were reported in hemophilia patients treated with concentrates before 1985 (Yee et al, 2000;Lee C, 2009;Manucci, 2008;Arnold et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence rates of HCV infection up to 100% were reported in hemophilia patients treated with concentrates before 1985 (Yee et al, 2000;Lee C, 2009;Manucci, 2008;Arnold et al, 2006). Even though the introduction of heat-treated factor concentrates progressively decreased HCV transmission, the true risk ended when new regulations in blood donor screening together with the implementation of second and third generation immunoassays for the detection of antibodies against HCV was introduced in 1991 in Europe, in 1992 in the US and 1993 in Argentina (Morfini et al, 1994;Franchini et al, 2001;Lee and Dusheiko, 2002;Tagliaferri et al, 2010;Argentinean Ministry of Health resolution #1077, 1993. However, it is important to notice that clotting factor concentrates used for Argentinean hemophilic patient treatments were never manufactured in the country but brought from the US or Europe.…”
Section: Introductionmentioning
confidence: 99%